Microdrop Size Measurement in a Mixing Unit Using Laser Technique - Al-Janabi, A. Hadi M.; Radha’a, Majid S.; Asker, Ali Z. (Iraqi Journal of Laser, 2003)
One of the troublesome duties in chemical industrial units is determining the instantaneous drop size distribution, which is created between two immiscible liquids within such units. In this work a complete system for measuring instantaneous droplet size is constructed. It consists of laser detection system (1mW He-Ne laser), drop generation system (turbine mixer unit), and microphotography system. Two immiscible liquids, water and kerosene were mixed together with different low volume fractions (0.0025, 0.02) of kerosene (as a dispersed phase) in water (as a continuous phase). The experiments were carried out at different rotational speed (1180- 2090 r.p.m) of the turbine mixer. The Sauter mean diameter of the drops was determined by laser light according to the scattering (attenuation) of the laser beam during passing through the emulsion. The same droplet which where examined by the laser beam, where tested also under microphotography system. The result showed that the laser detection technique gives drop diameter smaller than that obtained by photographing.